Identification of prevalent microbial communities in a municipal solid waste landfill - ÇALLI, BARIŞ; MERTOĞLU, BÜLENT; DURMAZ ŞAM, SELÇEN (I W A PUBLISHING, 2006)
To identify the microbial communities in Istanbul, Odayeri Municipal Solid Waste Landfill, leachate samples were collected from different sections at different stabilization phases. In identification of microbial communities in leachate samples, molecular techniques such as FISH, DGGE and cloning based on 16S rRNA and mcrA genes were used. As the chemical and microbiological compositions of the samples were compared, obvious correlations were found between the stability of the landfill section and abundance of active methanogens. On the other hand, there were considerable differences between acidogenic and mature leachate samples in DGGE profiles of archaeal and bacterial 16S rRNA genes. Moreover, in acidogenic leachate samples having BOD5/COD ratio of about 0.5 acetate utilizing Methanosarcina and Methanosaeta species were intensively detected in FISH. Although only very few H-2-utilizing methanogens were identified with FISH analysis, most of the clones isolated from mature leachate samples clustered within H-2-utilizing Methanobacteriales and Methanomicrobiales according to phylogenetic analysis of 16S rRNA and mcrA clones, respectively.
Keywords: acidogenic leachate; FISH; landfill; mcrA gene; methanogen; phylogenetic analysis; 16S RIBOSOMAL-RNA; ARCHAEAL COMMUNITY; METHANOGENIC ARCHAEA; DIVERSITY; LEACHATE; GENE